Perancangan Media Sosialisasi Tanggap Bencana Kabupaten Semarang Berbasis Animasi 2D - Dian Iskandar; Y.M. Tumimomor (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2017)
Indonesia is a prone are to the occurrence of disasters, this can be caused by natural factors and human factors. Disasters that occur often cause the impact of the material loss as well as the loss of life. To minimize the losses from the occurrence of disasters, it is necessary to arrange socialization with society in responding to a threatening disaster. Therefore, this research will discuss about the design of socialization media of disaster response for the people of Semarang Regency based on 2D animation. The object of this research is the Regional Disaster Management Agency of Semarang Regency. This research uses qualitative methods and linear strategy, which contains the design of animation from the beginning to the final form of 2D animation video as a media of disaster response socialization. The result is a disaster response socialization media presented in the form of 2D animation that contains information related to signs, prevention, and disaster management. Keywords: Video, Animation, Socialization, Disaster, BPBD Kabupaten Semarang.